Trauma laparotomy and damage control surgery. Issue 9 (September 2022) - Maclean, William; Levy, Bruce; Rockall, Timothy
Abstract: Abdominal trauma can result in multiple different injuries affecting a number of organs. Early recognition and management of these injuries will improve patient survival and morbidity. Appropriate intervention involves the use of either definitive or damage control surgery for both haemorrhage and peritonitis. This article discusses the different mechanisms of injury, early assessment and investigations. It goes on to highlight the features of a trauma laparotomy, its preparation, management and the systematic approach for damage control surgery. The main abdominal organs are outlined in more detail to describe the individual approach to them in trauma.